4
$\begingroup$

Let be $\alpha \in ]-1, 1[$ and $(u_n)_{n \in \mathbb{N}}$ a real-valued sequence.

Let us suppose that $(u_{n + 1} - \alpha u_n)_{n \in \mathbb{N}}$ converges. How to show that $(u_n)_{n \in \mathbb{N}}$ converges?

What I tried:

  • Work on $u_{n + 1} - u_n = (\alpha - 1) u_n + L + o(1)$ for some $L \in \mathbb{R}$ which would be the limit of $(u_{n + 1} - \alpha u_n)_n$ and use some kind of Cesaro sommation technique.
  • Consider the set of limits of all subsequences of $(u_n)_n$ and show that its lower bound is its upper bound (unsuccessful).
$\endgroup$
6
$\begingroup$

Write $a_n = u_n - \alpha u_{n-1}$ and notice that for any $0 < k < n$,

$$ u_n = a_n + \alpha a_{n-1} + \cdots + \alpha^{k-1}a_{n-k+1} + \alpha^{k} u_{n-k}. $$

Since $(a_n)$ converges, it is bounded by some $M_1 > 0$. Then the above formula with $k = n-1$ shows that

$$ \lvert u_n \rvert \leq \frac{M_1}{1-\alpha} + \lvert u_0 \rvert =: M_2, $$

which proves that $(u_n)$ is also bounded. Now let $\ell$ the limit of $(a_n)$ and fix a positive integer $N$. Then

\begin{align*} \left| u_n - \frac{\ell}{1-\alpha} \right| &= \left| \alpha^N u_{n-N} + \sum_{k=0}^{N-1} \alpha^k (a_{n-k} - \ell) - \frac{\alpha^N \ell}{1-\alpha} \right| \\ &\leq \alpha^N \left(M_2 + \frac{\lvert\ell\rvert}{1-\alpha}\right) + \sum_{k=0}^{N-1} \alpha^k \lvert a_{n-k} - \ell \rvert. \end{align*}

Taking limsup as $n\to\infty$, we have

$$ \limsup_{n\to\infty} \left| u_n - \frac{\ell}{1-\alpha} \right| \leq \alpha^N \left(M_2 + \frac{\lvert\ell\rvert}{1-\alpha}\right). $$

Since the left-hand side is independent of $N$, we may let $N\to\infty$ to show that the limsup is indeed $0$. Therefore $u_n$ converges to $\ell/(1-\alpha)$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.